Learning from wildfire: co-creating knowledge using an intersectional feminist standpoint methodology - Elliott, Tina M.; Reed, Maureen G.; Fletcher, Amber J. (Frontiers in Environmental Science, 2023)
Due to climate change, rural Canadian communities living in boreal regions can expect more intense and frequent wildfires. People's experiences of wildfire hazards are differentiated by intersecting social factors such as age, gender, culture, and socio-economic status, as well as by social structures that enable or limit adaptation. This study engaged two Northern Saskatchewan communities in a process of co-developing a post-disaster learning framework and companion guidebook to support ongoing adaptation to climate hazards, enabled by the use of an intersectional feminist standpoint methodology. This methodology influenced both the process and outcomes of the research, which involved 18 interviews conducted with study community members and a workshop with a subset of the interview cohort. The intersectional feminist standpoint methodology facilitated insight into how intersecting social identity factors (e.g., gender, age, socio-economic status, and geography) shaped experiences of wildfire, as well as the need for and potential of post-disaster learning at the community level. In this paper, we focus on methodological insights for researchers and communities who seek to co-create knowledge and learning opportunities. In particular, we note the methodological impacts on research design choices, learning through the research process, and lessons learned through conducting community-engaged research during the early days of another kind of crisis: the COVID-19 pandemic.Research designTwo communities were engaged in this study: Wadin Bay and Napatak (see Figure 1). These communities are located in Northern Saskatchewan (SK), Canada, each approximately 25 kilometers from the northern town of La Ronge, SK in Treaty 6 Territory. These rural communities have